Scenarios and Options for Productivity Growth in Philippine Agriculture: An Application of the Agricultural Multimarket Model for Policy Evaluation (AMPLE) - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2010)
Sustaining and accelerating agricultural growth remains a development imperative in view of persistent rural poverty and emerging threats to food security. While growth can be achieved by expansion of agricultural area and input intensification, growth through improvement in productivity is a promising option. However, productivity growth appears to be a relatively low priority for policy. Rather, the agricultural strategy is oriented toward domestic protection to achieve self-sufficiency and to support production by generous subsidies. In contrast, an alternative strategy may be one that is competition-oriented and productivity-based, i.e., one that favors integration with the international economy through trade, as well as making domestic investments targeted at productivity growth. Scenarios for Philippine agriculture under these policy options are evaluated using a new supply and demand model (Agricultural Multimarket Model for Policy Evaluation or AMPLE). Model simulations suggest that: rapid productivity growth, even when combined with trade liberalization, is generally favorable for farmers and consumers based on improved outlook on production, exports, and food consumption. In contrast, trade liberalization alone has a contractionary effect on agriculture; and production support is a costly instrument for promoting agricultural growth. The model experiments suggest that a back-to-basics strategy for agriculture, incorporating various productivity-based instruments such as investments in R&D, extension, rural infrastructure, protection of the resource base of agriculture, and even human capital formation and institutional reforms, are key to long-term agricultural growth.
Keywords: 330; Philippines; agriculture; productivity growth; scenario analysis; supply and demand; technological change; Agrarproduktion; Technischer Fortschritt; Agrarpolitik; Wirkungsanalyse; Szenariotechnik; Philippinen